The Association Between Medication Adherence and Drug-Related Problems (DRPs) with Clinical Outcomes of Diabetes Patients at Public Health Center in Salatiga - Hati, Anita Kumala; Yasin, Nanang Munif; Kristina, Susi Ari (Faculty of Pharmacy, Universitas Gadjah Mada, 2026)
Background: Diabetes mellitus (DM) is a disease whose clinical condition can be controlled. The clinical outcomes of DM patients are an important parameter for successful treatment and are influenced by many factors.Objectives: This study aimed to analyze the relationship between medication compliance and drug-related problems (DRPs) with the clinical outcomes of diabetes patients at three Primary Health centers in Salatiga.Methods: An observational study method was adopted with prospective data collection from the medical records and medication compliance observation of type 2 diabetes mellitus (T2DM) patients, in October 2023–April 2024. DRP analysis was based on categories Cipolle, 2012, and medication compliance was measured using the pill count method. Data analysis was conducted using the Spearman test to assess the correlation between medication adherence and HbA1c levels, as well as the occurrence of DRP.Results: A total of 40 subjects participated in this study, with the largest gender being female (72.5%), and hypertension was the most common comorbid condition (55%). The highest compliance rate in patients was 40% and DRP events were detected in 107 cases. The difference in patient HbA1c levels at baseline and the 3rd month showed a significant difference, and 67.5% experienced an increase. Furthermore, there was a strong relationship between compliance and HbA1c achievement (sig = 0.003, r = 0.452), as well as between the incidence of DRP and HbA1c achievement (sig = 0.000, r = 0.644).Conclusion: Compliance and DRPs influenced the HbA1c levels of T2DM patients in PROLANIS across three Public Health Centres in Salatiga.